A bibliometric and visualized research on global trends of abdominoplasty, 2011–2021. (20th September 2022) - Xi, Tingting; Guo, Rong; Wu, Xuemei; Jiang, Hua; Xiong, Jiachao
Abstract: Objectives: Patients with multiple pregnancies, multiple pregnancies, and a history of severe obesity, the abdominal wall muscles, and skin exhibit rectus abdominis separation and skin laxity due to prolonged overstretching, which causes damage to both the patient's appearance and health. Abdominoplasty is a surgical solution to the problems of separation of the rectus abdominis muscle and laxity of the skin of the abdominal wall under direct vision, which is important for patients with the above problems. Currently, many studies have been reported on abdominoplasty, however, no reverent bibliometric analyses of abdominoplasty have been published. Methods: In this study, we screened 1, 119 studies on abdominoplasty between 2011 and 2021 based on the Web of Science Core Collection (WOSCC) database and performed a bibliometric analysis. Results: We found that high‐quality research related to abdominoplasty has increased in the last decade, and the United States was the leading country in the field of abdominoplasty. Stanford university ranked first in number of publications and citations. Aesthetic surgery journal was the most productive journal, followed by the Plastic and reconstructive surgery and Aesthetic plastic surgery. In addition, bariatric surgery, venous thromboembolism, rectus diastasis, breast reconstruction and umbilicoplasty are the keywords of recent publications that are the focus of current research. Conclusion: This study provides a comprehensive analysis and visualization of global research trends on abdominoplasty from 2011 to 2021, and improvements in abdominoplasty to reduce the incidence of postoperative complications will remain a focus of future research.